Distribution of Insecticide Resistance Genetic Markers in the West Nile Virus Vector Culex pipiens from South-Eastern Romania - Ioana Georgeta Stancu; Florian Liviu Prioteasa; Georgiana Victorița Tiron; Ani Ioana Cotar; Elena Fălcuță; Daniela Porea; Sorin Dinu; Cornelia Svetlana Ceianu; Ortansa Csutak (Insects, 2022)
Culex pipiens pipiens and Culex pipiens molestus mosquitoes are the vectors of West Nile virus in south-eastern Romania, an area of intense circulation and human transmission of this virus. The level of insecticide resistance for the mosquito populations in the region has not been previously assessed. Culex pipiens mosquitoes collected between 2018 and 2019 in south-eastern Romania from different habitats were subjected to biotype identification by real-time PCR. Substitutions causing resistance to organophosphates and carbamates (F290V and G119S in acetylcholinesterase 1) and to pyrethroids (L1014F in voltage gated Na+ channel) were screened by PCR or sequencing. Substitutions F290V and G119S were detected at very low frequencies and only in heterozygous state in Culex pipiens molestus biotype specimens collected in urban areas. The molestus biotype population analysed was entirely homozygous for L1014F, and high frequencies of this substitution were also found for pipiens biotype and hybrid mosquitoes collected in urban and in intensive agriculture areas. Reducing the selective pressure by limiting the use of pyrethroid insecticides only for regions where it is absolutely necessary and monitoring L1014F mutation should be taken into consideration when implementing vector control strategies.